Association of Plasma Transferrin With Cognitive Decline in Patients With Mild Cognitive Impairment and Alzheimer’s Disease - Guan, Jingjing; Wang, Peng; Lu, Liping; Zhao, Guanan (Frontiers in Aging Neuroscience, 2020)
Objective: To examine whether plasma transferrin levels are associated with longitudinal changes in cognitive performance in older individuals with normal cognition (CN), mild cognitive impairment (MCI), and mild Alzheimer’s disease (AD). Methods: At baseline, there was a total of 358 participants from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort, including 58 older individuals with CN, 198 older individuals with MCI, and 102 patients with AD. Linear mixed models were utilized to examine the associations of plasma transferrin levels with changes in cognitive performance over time after adjustment of several potential covariates. The mini-mental state examination (MMSE) and clinical dementia rating scale-sum of boxes (CDR-SB) were used to examine the global cognition of participants. Results: First, no significant differences in plasma transferrin levels were observed across three diagnostic groups. Second, in the cross-sectional analyses, baseline plasma transferrin levels were negatively associated with MMSE scores in the CN group, but not the MCI or AD group. Third, in the longitudinal analyses, we found that higher plasma transferrin was associated with a steeper cognitive decline in the MCI and AD groups, but not the CN group. Conclusion: Higher plasma transferrin levels were associated with a steeper cognitive decline in participants with MCI and AD.